Impelementasi Kitab Wasiyatul Musthofa dalam Mendisiplinkan Shalat Jamaah di Usia Remaja - Ramadhan, Ahmad Muhammad; Masnawati, Eli (Asian Journal of Islamic Studies and Da'wah, 2024)
Prayer is an act of worship that must be carried out by Muslims, including adolescents who have experienced wet dreams, at this time adolescents often experience laziness to pray, including the five daily prayers performed in congregation. This is caused by various factors, such as the influence of socialization, laziness, and busyness with other activities. The book of Wasiyatul Musthofa by Sheikh Abdul Wahab As-Sya'roni is a book that contains a collection of advice from the Prophet Muhammad SAW. One of the advice contained in this book is about the importance of congregational prayer. In this book, the Prophet Muhammad SAW mentioned that congregational prayer has many virtues, both in the world and in the hereafter. This research uses a qualitative approach using the library research method. Primary data sources are obtained from the book of Wasiyatul Musthofa, while secondary data are journals, books, and articles related to the research being discussed. The results showed that the book of Wasiyatul Musthofa contains various instructions and advice that can be used to discipline congregational prayer in adolescence. Some of these instructions and advice include: Getting used to praying in congregation from an early age. explaining the wisdom and virtues of congregational prayer. Encourage teenagers to follow the example of parents and teachers who diligently pray in congregation. Strive for a safe environment for the implementation of congregational prayer. This study concludes that the book of Wasiyatul Musthofa can be one of the reference sources for parents, teachers, and adolescents in disciplining congregational prayer.